Unknown Risk Factor in Pediatric Ischemic Stroke: Challenges in A Developing Country - Edeline Samudra; Retno Jayantri Ketaren (Magna Neurologica, 2026)
Background: Stroke is a sudden neurological disturbance with high mortality rates in both children and older people. Pediatric stroke is rare but can lead to lifelong disability due to the immaturity of the brain, and its management can be challenging. Case: A 23-year-old female presented with a history of right-sided weakness and spasticity that began 11 years ago and improved over the past two years. Risk factors that could be excluded were ruled out, while congenital disorders could not be investigated due to financial constraints. Diagnosed with non-hemorrhagic stroke at age 12, an MRI revealed an old infarct in the left internal capsule. The absence of known risk factors underlying her ischemic stroke made a congenital disorder a plausible diagnosis. She was given botulinum toxin type A (BoNT-A) injections to manage spasticity, and her symptoms improved. In the past year, she developed mood disturbances and sleep difficulties, which were treated with quetiapine. Discussion: The pediatric brain is metabolically more active with higher cerebral blood flow demands, making it more susceptible to focal neurological injuries. Most pediatric strokes are ischemic, with numerous potential risk factors including cardiac issues, vasculopathy, coagulopathies, infections, and congenital disorders with vascular complications. Treatment for pediatric ischemic stroke is similar to that in adult cases. In this patient, BoNT-A injections reduced acetylcholine release, effectively treating the patient’s spasticity. Conclusion: Stroke can occur at any age, with pediatric strokes potentially resulting in worse outcomes. Therefore, thoroughly evaluating diverse potential etiologies, including congenital disorders, is crucial.